The Effect of Employee Training and Development on Employee Performance - Putri Wulansari; Muhammad Mathori (Research Horizon, 2026)
Human resources are one of the most essential assets within an organization that must be effectively managed to enhance performance and achieve organizational objectives. This study examines the importance of enhancing employee performance, which continues to experience issues related to punctuality, service quality, and employee initiative. The research employs a quantitative approach using a causal-associative method and is analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the support of SmartPLS 3.2.9 software. The population consists of all 60 employees, with a saturated sampling technique applied so that the entire population serves as the sample. Data were collected via a structured questionnaire utilizing a Likert scale. The results indicate that training exerts a positive and significant effect on employee performance, employee development has a positive and significant impact on performance, and, simultaneously, training and development collectively exert a positive and significant influence on employee performance. The implications of this study highlight the importance for organizations to design and manage training and development programs in a continuous and integrated manner, ensuring employees are equipped not only to meet current job demands but also to take on greater responsibilities in the future.